The effects of a 7-week practical blood flow restriction program on well-trained collegiate athletes. - Luebbers, P. E.; Fry, A. C.; Kriley, L. M.; Butler, M. S. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the effects of a 7-week practical blood flow restriction (BFR) protocol used in conjunction with a strength training program on measures of muscular strength and size in collegiate American football players. Sixty-two participants were divided into 4 groups. Three groups completed a traditional upper- and lower-body split strength program. Two of these groups also completed supplemental lifting sessions. Of these 2, 1 completed the additional lifts with BFR. The final group completed a modified training program, followed by the supplemental lifts, with BFR. The supplemental lifting protocol consisted of bench press and squat, using 20% 1 repetition maximum (1RM) for 4 sets with 30 repetitions performed in the first set and 20 repetitions performed in the following 3 sets. Each set was separated by 45 seconds of rest. The supplemental bench press was completed at the end of upper-body days and the squat at the end of lower-body days. Dependent measures were taken before the start of the program and again on conclusion the following dependent variables were measured: upper- and lower-body girths, 1RM bench, and squat. Results of a 4 × 2 mixed-model multivariate analysis of covariance revealed a significant difference for the interaction on the dependent variables. Follow-up univariate analysis of variances indicated a significant difference for 1RM squat. This suggests that a practical BFR program used in addition to a traditional strength training program can be effective at increasing 1RM squat performance. The use of elastic knee wraps makes BFR a feasible training option for coaches and athletes.